Computer‐based testing and the 12‐item Screener and Opioid Assessment for Patients with Pain‐Revised: A combined approach to improving efficiency. Issue 1 (8th August 2018) - Finkelman, Matthew D.; Jamison, Robert N.; Magnuson, Britta; Kulich, Ronald J.; Butler, Stephen F.; Smits, Niels; Weiner, Scott G.
Abstract: Objectives were to combine computer‐based stopping rules with the 12‐item form of the Screener and Opioid Assessment for Patients with Pain‐Revised (SOAPP‐R), and to compare this combined procedure with the full‐length (24‐item) SOAPP‐R, the computer‐based stopping rules alone, and the 12‐item short form alone. Three datasets were analyzed, including data from 428 subjects from the initial or cross‐validation studies of the SOAPP‐R; 84 patients from a pain center; and 110 primary care patients. Subjects completed the full‐length SOAPP‐R and were assessed for aberrant medication‐related behaviors. A real‐data simulation was conducted to determine the screening characteristics and mean test length of each version of the SOAPP‐R. One procedure combining stochastic curtailment with the 12‐item short form reduced the mean length by 37% to 42% compared to the short form alone; by 42% to 45% compared to stochastic curtailment alone; and by 68% to 71% compared to the full‐length form. The combined procedure had lower mean test lengths, and equal screening characteristics, compared to a procedure coupling curtailment with the 12‐item short form. A procedure combining computer‐based stopping rules with the 12‐item short form of the SOAPP‐R has potential to enhance the efficiency of the screener.